2004
DOI: 10.1001/jama.292.12.1454
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Including Walking, and Cognitive Function in Older Women

Abstract: Context Physical activity may help maintain cognitive function in older adults. Objective To examine the relation of long-term regular physical activity, including walking, to cognitive function. Design Women reported participation in leisure-time physical activities on biennial mailed questionnaires beginning in 1986. We assessed long-term activity by averaging energy expenditures from questionnaires in 1986 through participants' baseline cognitive assessments (1995 to 2001). We used linear regression to esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
450
6
17

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 969 publications
(511 citation statements)
references
References 48 publications
38
450
6
17
Order By: Relevance
“…The results of this study, in which only a dozen participants did not exercise at all, cannot be seen as providing support for other reports that regular exercise is associated with less cognitive decline associated with aging [34] [35]. However, many other studies have reported significant improvements in cognitive functioning in association with regular aerobic exercise [36] [37].…”
Section: Discussionsupporting
confidence: 63%
“…The results of this study, in which only a dozen participants did not exercise at all, cannot be seen as providing support for other reports that regular exercise is associated with less cognitive decline associated with aging [34] [35]. However, many other studies have reported significant improvements in cognitive functioning in association with regular aerobic exercise [36] [37].…”
Section: Discussionsupporting
confidence: 63%
“…This observation is particularly interesting in light of studies suggesting that the dentate gyrus is a hippocampal subregion differentially vulnerable to the aging process, as shown in humans (39,40), nonhuman primates (30,41), and rodents (30,42), and that dentate gyrus dysfunction contributes to cognitive aging (30,40). Interestingly, a growing number of studies have established that exercise ameliorates age-related cognitive decline (43)(44)(45)(46). Thus, the effect that exercise was observed to have on the dentate gyrus likely contributes to the reported cognitive benefits exercise has on the aging brain.…”
Section: Discussionmentioning
confidence: 91%
“…A study examining physical activity and dementia did not find a significantly reduced risk for those participating in over 5 h per week of exercise (Chang et al 2010). Alternatively, the protective effect may be cumulative as higher levels of activity showed less cognitive decline in a study of women aged 70 years and older performing regular physical activity for 8 to 15 years (Weuve et al 2004). Even in this study, however, walking at an easy pace ≥1.5 h/week was associated with a significantly better cognitive performance.…”
Section: Discussionmentioning
confidence: 99%
“…Populationbased studies of older adults have reported a slower rate of decline in cognitive function among those engaged in higher levels of physical activity at baseline (Ku et al 2012;Lytle et al 2004;Weuve et al 2004;Yaffe et al 2001). In a meta-analysis of prospective studies involving people aged 65 years and older, physical activity at both high and low-to-moderate levels was found to lower the risk of cognitive decline (Sofi et al 2011).…”
Section: Introductionmentioning
confidence: 99%